Meeting Report: South African Medical Research Council Standard of Care in Clinical Research in Low- And Middle-Income Settings Summit, November 2017 - Miner, Maurine; Bekker, Linda-Gail; Kredo, Tamara; Bhagwandin, Niresh; Corey, Lawrence; Gray, Glenda (My University, 2020)
Introduction: The South African Medical Research Council (SAMRC) convened a summit to discuss issues relating to standard of care (SoC) in HIV prevention clinical trials, both for treatment and prevention of disease. Policymakers, regulators, ethicists, experts in the law (as it pertains to medical research), researchers, representatives of advocacy groups, and the HIV Vaccine Trials Network (HVTN) presented a framework within which SoC principles could be articulated. Discussion: Summit participants discussed how and when to include new modalities of HIV treatment and prevention into existing clinical practice guidelines, and by extension in clinical trial protocols. Participants involved in the execution of care and the scale-up of new interventions, in particular, the roll out of pre-exposure prophylaxis (PrEP), presented the opportunities for and challenges to scaling up interventions, and their experience with demonstration projects of PrEP. Advocates and community members propagated the need to make interventions that could avert HIV infection available as soon as possible. Experts in evidence-based guideline development discussed the nuances in evaluating evidence for policy and the mechanisms for getting medicines on the Essential Medicines List in South Africa. Given the variability in clinical trial efficacy of PrEP amongst different populations, scientists and statisticians discussed the various biological, virological and immunological reasons for this heterogeneity. Conclusions: Input was given as to the impact of introducing PrEP in other HIV prevention trials, and the considerations for the design of both antiretroviral (ARV)-based and non-ARV based HIV prevention trials. The meeting recommended supporting access to PrEP in HIV prevention trials by 1) developing PrEP access plans for HIV vaccine trials; 2) creating a PrEP fund that would supply PrEP to sites conducting HIV prevention trials via a central procurement mechanism; and 3) support the safety monitoring of PrEP.
Keywords: Pre-exposure prophylaxis; South Africa; standard of care; LMIC; HIV/AIDS; clinical trials